Holopelagic Annelida from the Red Sea off the Central Saudi Arabian coast - Kolbasova, G.d.; Syomin, V.l.; Sempere-Valverde, J.; Teixeira, M.a.l.; Carvalho, S. (Zootaxa, 2025)
Pelagic polychaetous annelids were collected in the vicinity of King Abdullah University of Science and Technology (Saudi Arabia) in December 2023 and April 2024. In total, 11 species belonging to four taxa were found: Krohnia cf. lepidota, Vanadis minuta, Plotohelmis cf. capitata (tribe Alciopini), Pelagobia longicirrata (fam. Lopadorrhynchidae), Typhloscolex cf. muelleri, T. robustus, Typhloscolex sp., Sagitella kowalewskii, Sagitella dubia comb. nov. (fam. Typhloscolecidae), Tomopteris rolasi and T. planktonis (fam. Tomopteridae). Molecular markers 18S and 28S indicate that V. minuta may be a complex of two species. Travisiopsis dubia, according to these markers, belongs to the genus Sagitella; therefore, we amended the diagnosis of the genus Sagitella to include this species. The genus Typhloscolex in our samples is represented by three species. The first one, T. robusta, is represented here as T. robustus, due to the gender variable adjective with incorrect original feminine ending. The second species T. cf. muelleri is morphologically indistinguishable from T. muelleri from the Atlantic; however, they form separate clades in the phylogenetic tree. The third species Typhloscolex sp. is new to science, but we do not describe it formally here because to condition of the material is insufficient for morphological examination.